A critical reflection on the Commission on Religious Education’s proposed National Entitlement to Religion and Worldviews in England and Wales - Salter, Emma (Journal of Religious Education, 2021)
This paper responds to the Commission on Religious Education’s proposed National Entitlement to Religion and Worldviews in England and Wales. Qualitative data were collected from nine English primary Religious Education (RE) teachers to establish their responses to the proposed National Entitlement from their perspectives as RE practitioners. Findings show that teachers were supportive of the high ambitions the National Entitlement has for RE, that they saw opportunities for pupils’ social and personal development as well as advancement in substantive knowledge, but that they were concerned about content-heavy curricula and structural barriers to implementing the National Entitlement. In response, the paper examines ‘cumulatively sufficient’ curricular design and ‘pedagogical reduction’ as strategies to activate the National Entitlement, and raises questions about ‘instrumental purposes’ in the conceptualisation of Religion and Worldviews. The paper recommends sharper account of the originality of Religions and Worldviews in order to advance the cause of the National Entitlement.